Which Policy to Which Family? The Answers to New Social Risks in Three Welfare Systems - Marta Feletto (Luxembourg Income Study (LIS), 1999)
Radical employment, household structure and stability transformations have created new tensions on the welfare state front, whose social programs were constructed in an era with a wholly different risk profile. Rowntree's poverty cycle clearly exemplifies the postwar picture of an exceptional low risk of economic deprivation in the active phase of life cycle, due to decisive factors as well-functioning, full-employment labor markets and stable and fertile families. Since 1970s, because of the increasing family instability and the rising structural unemployment and inequality in wages and incomes, western welfare states have found their safety nets straining under the burden of expanding number of working age families. Market and family concomitant 'failure' is a major catalyst of poverty and the risk of social exclusion and economic insecurity entrapment are considerable. Here, however, welfare states' design make a difference, to the extent that it has rethought traditional assumption on work, family and social risks. The key issue, we find, is in the readiness or reluctance to create, through government, a foundation of income or to supplement earned income or other benefits to families and their successful performance in the labor market. I concentrate on three western settings, each characterized by strong diversities in the resource distribution systems (family, labor market and welfare) and by a different level of economic deprivation: Italy, Sweden and the United States. They nonetheless identify ideal-typical representations of Esping-Andersen's conservative, social-democratic and liberal regimes, respectively (Esping-Andersen, 1990).
Keywords: 330; Sozialpolitik; Familienleistungsausgleich; Weibliche Arbeitskräfte; Alleinerziehende; Italien; Schweden; USA